Estrogen receptor 2b deficiency impairs the antiviral response of zebrafish. Issue 1 (November 2015) - López-Muñoz, Azucena; Liarte, Sergio; Gómez-González, Nuria E.; Cabas, Isabel; Meseguer, José; García-Ayala, Alfonsa; Mulero, Victoriano
Abstract: Although several studies have demonstrated the ability of some endocrine disruptive chemicals (EDCs) to alter the physiology of zebrafish, the immune–reproductive interaction has received little attention in this species. In this study, we used a homozygous line carrying an insertion of 8 amino acids in the ligand-binding domain of the estrogen receptor 2b gene ( esr2b ) to further understand the role of estrogen signaling on innate immunity. Adult mutant fish showed distorted sexual ratios related with alterations in testicular morphology and supraphysiological testosterone and 17β-estradiol (E2) levels. Immunity-wise, although esr2b mutant fish showed unaltered antibacterial responses, they were unable to mount an effective antiviral response upon viral challenge. RT-qPCR analysis demonstrated that mutant fish were able to induce the genes encoding major antiviral molecules, including Ifnphi1, Ifnphi2, Infphi3, Mxb and Mxc, and the negative feedback regulator of cytokine signaling Socs1. Notably, although esr2b mutant larvae showed a similar resistance to SVCV infection to their wild type siblings, waterborne E2 increased their viral susceptibility. Similarly, the exposure of adult wild type zebrafish to E2 also resulted in increased susceptibility to SVCV infection. Finally, the administration of recombinant Ifnphi1 hardly reversed the higher viral susceptibility of esr2b mutant zebrafish, suggesting that elevated socs1 levels impair Ifn signaling. All together, these results uncover an important role for E2 and Esr signaling in the fine-tuning of sexual hormone balance and the antiviral response of vertebrates. Highlights: Adult esr2b mutant fish showed distorted testicular physiology. Adult esr2b mutant fish were unable to mount an effective antiviral response. Adult esr2b mutant fish showed increased expression of socs1 upon viral challenge. Estradiol treatment increased the viral susceptibility of both adult and larvae. Recombinant Ifnphi1 hardly reversed the higher viral susceptibility of esr2b mutants.